Taxonomic review of the Cataglyphis livida complex (Hymenoptera, Formicidae), with a description of a new species from Iran - Sebastian Salata; Haniyeh Kiyani; Kambiz Minaei; Lech Borowiec (ZooKeys, 2021)
Cataglyphis fici sp. nov., a member of the Cataglyphis livida complex, is described from the Estahban county of south-western Iran. The species is characterized by small body size and yellow to yellowish red body coloration with distinctly infuscated legs. Additionally, the taxonomic status of all known members of the Cataglyphis livida complex is updated. Cataglyphis lutea Pisarski, 1967, stat. rev. is raised to the species level and Cataglyphis viaticoides (André, 1881) is proposed as a senior synonym of Cataglyphis livida bulgarica Atanassov, 1982, syn. nov. and Cataglyphis albicans mixtus (Forel, 1895), syn. nov. Finally, a provisional key to members of the livida complex is provided.